PI3K‐AKT‐FOXO1 pathway targeted by skeletal muscle microRNA to suppress proteolytic gene expression in response to carbohydrate intake during aerobic exercise - Margolis, Lee M. (Physiol Rep, 2018)
Ingesting protein and carbohydrate together during aerobic exercise suppresses the expression of specific skeletal muscle microRNA and promotes muscle hypertrophy. Determining whether there are independent effects of carbohydrate and protein on microRNA will allow for a clearer understanding of the mechanistic role microRNA serve in regulating skeletal muscle protein synthetic and proteolytic responses to nutrition and exercise. This study determined skeletal muscle microRNA responses to aerobic exercise with or without carbohydrate, and recovery whey protein (WP). Seventeen males were randomized to consume carbohydrate (CHO; 145 g; n = 9) or non‐nutritive control (CON; n = 8) beverages during exercise. Muscle was collected before (BASE) and after 80 min of steady‐state exercise (1.7 ± 0.3 V̇O(2) L·min(−1)) followed by a 2‐mile time trial (17.9 ± 3.5 min; POST), and 3‐h into recovery after consuming WP (25 g; REC). RT‐qPCR was used to determine microRNA and mRNA expression. Bioinformatics analysis was conducted using the mirPath software. Western blotting was used to assess protein signaling. The expression of six microRNA (miR‐19b‐3p, miR‐99a‐5p, miR‐100‐5p, miR‐222‐3p, miR‐324‐3p, and miR‐486‐5p) were higher (P < 0.05) in CHO compared to CON, all of which target the PI3K‐AKT, ubiquitin proteasome, FOXO, and mTORC1 pathways. p‐AKT(T) (hr473) and p‐FOXO1(Thr24) were higher (P < 0.05) in POST CHO compared to CON. The expression of PTEN was lower (P < 0.05) in REC CHO than CON, while MURF1 was lower (P < 0.05) POST CHO than CON. These findings suggest the mechanism by which microRNA facilitate skeletal muscle adaptations in response to exercise with carbohydrate and protein feeding is by inhibiting markers of proteolysis.